Evaluation of the Effectiveness of Dragon Tail Leaf Extract (Rhaphidophora pinnata (Lf) Schott) on Incisional Wound Healing in White Rats (Rattus norvegicus) - Joke L. Tombuku; Kristin Mosso; Jeane Mongi; Nerni O. Potalangi; Hanna M. Rumagit; Rahmat Santoso; Amal R. Ginting (Biofarmasetikal Tropis (The Tropical Journal of Biopharmaceutical), 2025)
Rhaphidophora pinnata (dragon tail leaf) has traditionally been used as a medicinal plant for treating wounds. This research aimed to evaluate the effectiveness of Rhaphidophora pinnata leaf extract on incision wound healing in male white rats (Rattus norvegicus). The study employed a laboratory experimental design using 15 rats divided into five treatment groups: negative control (aquades), positive control (povidone iodine), and topical extract concentrations of 15%, 20%, and 25%. Wound length was measured daily for 14 days. Statistical analysis using paired sample t-test showed a significant difference between pre-treatment and post-treatment wound conditions (p = 0.000 < 0.05; t = 5.391). The results demonstrated that all extract concentrations accelerated wound closure, with the 25% concentration showing the greatest healing effect and complete wound closure by day 14. These findings indicate that Rhaphidophora pinnata leaf extract is effective in promoting incision wound healing, particularly at a concentration of 25%.